Improving on Nature: The Role of Nanomedicine in the Development of Clinical Natural Drugs - Bilia, Anna Rita; Piazzini, Vieri; Guccione, Clizia; Risaliti, Laura; Asprea, Martina; Capecchi, Giada; Bergonzi, Maria Camilla (Planta Medica, 2017)
Natural products have been used as a major source of drugs for millennia, and about half of the pharmaceuticals in use today are derived from natural products. However, their efficacy can be limited because of their low hydrophilicity and intrinsic dissolution rate(s), or physical/chemical instability. In addition, they can present scarce absorption, poor pharmacokinetics and bioavailability, scarce biodistribution, first-pass metabolism, trivial penetration and accumulation in the organs of the body, or low targeting efficacy. Novel nanoformulations based on drug delivery systems, namely nanoparticles, micelles, and vesicles, offer significant promise in overcoming these limitations. Nowadays, nanomedicine is crucial in developing appropriate therapeutic treatments of essential drugs, specifically antitumor and antiparasistic agents (i.e., Taxol, vincristine, camptothecin, doxorubicin, artemisinin) and other emerging molecules with pleiotropic functions (i.e., resveratrol, curcumin, salvianolic acid B, honokiol). Additionally, the number of nanoformulations developed with flavonoids, in particular rutin, quercetin, silymarin, and green tea catechins, is constantly increasing, and a significant number of publications have appeared in the last decade pertaining to nanoformulations based on extracts and essential oils. Most of these studies report very promising nanoformulations with sustained release and improved bioavailability at much lower doses than conventional preparations, and in many cases, also a better safety profile.
Keywords: nanomedicine; nanoparticles; micelles and vesicles; artemisinin; curcumin; salvianolic acid B; silymarin